Front Matter (Journal of the Assembly for Expanded Perspectives on Learning, 2003)
Editors' Message Surrounded by the dead he had caused through his wanton murder of an albatross, the tortured mariner of Samuel Taylor Coleridge fame watches the water snakes beyond the shadow of his ghost ship and “blessed them unaware./The selfsame moment I could pray; And from my neck so free/The Albatross fell off, and sank/Like lead into the sea” (ll. 287-291). Without deliberately looking, he suddenly recognizes the beauty of all creatures and blesses them “unaware.” The sailor experiences a serendipitous moment, and through that accidental wisdom frees himself from his self-created purgatory. Serendipity: Teaching for Accidental Wisdom serves as the theme for our ninth volume of JAEPL. The essays in this volume reflect in various ways the felicitous union of chance and sagacity, emphasizing that the excitement of serendipity is a necessary dynamic in our teaching, reading, and writing. A term coined by Horace Walpole in 1754, serendipity is a combination of blunder and perspicuity. Walpole introduces the “very expressive word serendipity” in a letter to a friend; he derives the neologism from a “silly fairy tale” about the three princes of Serendip [modern Sri Lanka] who “were always making discoveries, by accidents and sagacity, of things which they were not in quest of” (qtd. in Boyle). A serendipitous discovery results when something important not sought is found. John Barth in The Last Voyage of Somebody the Sailor notes that “it [Serendip] could never be reached by plotting a course directly for it, but only by sailing in good faith for elsewhere and losing one’s bearings” (504). But, in addition to losing your bearings, you have to have the wisdom to recognize the importance of what you discover. So serendipity depends on three elements: accident, a prepared mind, and the wisdom to recognize what one stumbles upon. Thus, we have Columbus’s discovery of America, the rabies vaccine by Pasteur, and dynamite by Nobel, all serendipitous discoveries (Royston). We open our celebration of serendipity with Spiritual Identities, Teacher Identities, and the Teaching of Writing. Kilian McCurrie explores the accidental wisdom that results from the intersection of his spiritual and teaching identities, a fusion that fosters a pedagogy of “original blessing” wherein teaching begins with the individual student’s commitment to self and community. While teaching and spirituality both hold within them the potential and need for serendipity, happy accidents are also central to our textual explorations. Robert Root in The Experimental Art highlights the happy union of form and content in creative nonfiction. Regardless of our formulas, he argues, creative nonfiction is an experimental art, one governed by felicitous sightings that return our attention to writerly concerns. Geographical as well as spiritual and textual travelers also make serendipitous discoveries as Candace Walworth recounts in Women in Black. Traveling home from Naropa University where she teaches, Walworth comes upon a group of women all dressed in black, silently inhabiting a street corner in Boulder, Colorado. They hold a lone banner pleading for peace. This discovery draws Walworth into joining them and weaving their silent protest into the Buddhist activism at the heart of her belief system. Serendipity is not just accidental discovery, whether pedagogical, spiritual, textual, or geographical. A central element of serendipity is preparation: the mind must be poised or prepared to recognize the wisdom that accident reveals. The essays by Laura Milner, Christina Vischher Bruns, and Kia Richmond highlight ways in which we can prepare ourselves for the grace of accidental wisdom. In Compos(t)ing Loss, Laura Milner helps up ready our minds and souls for healing in the face of deep loss. The metaphor of composting—the art of transforming decaying matter into rich and fertile life—serves to organize her essay in which she argues that writing helps students and teachers transmute pain and loss into acceptance and new beginnings. Christina Vischher Bruns in Encounters explores the vagaries of literary theories and, in the process, stumbles over an insight that enables her to unify these disparate stances and shape a teaching philosophy. She argues that we can prepare ourselves and our students for literature by focusing on Martin Buber’s I-Thou, a relationship that embraces the intersecting lines of text, author, and reader. Returning to a disturbing moment in her classroom, Kia Richmond in An Unspoken Trust—Violated emphasizes the necessity of reflection in the life of a teacher. Beginning with a “successful” classroom lesson that catapults her into a consideration of the connection between our values and our teacher identities, Richmond calls us to a reflective stance, one that enables us to perceive the overlap between who we think we are and how we teach. Finally, serendipity can be fostered in our classrooms by making spaces that invite happy discoveries, spaces that become wise places. In their careful study of nontraditional prewriting experiences in elementary grades, Carolyn L. Piazza and Christine Jecko in Multiple Forms of Prewriting in Elementary Writing Lessons point to non-mainstream strategies that enable students to draw on multiple literacies as they generate ideas in writing. They point to the ways in which art, role playing, music, dreamwork, and meditation can help students make their own happy discoveries. Finally, we return full circle to community and spirituality. W. Keith Duffy in Community, Spirituality, and the Writing Classroom enriches the discussion of community building in the composition classroom by suggesting that community results when we allow ourselves to be “found” by another. Drawing on Ernest Kurtz and Katherine Ketcham, Duffy argues that a wise place is one which allows community to be as well as to be built, a realization that requires him to embrace an attitude of openness so that he, too, can be found by his students. The excitement, lure, and reward of writing, reading, and teaching lie not only in what we expected to find but also in what we don’t expect to find…but do. Our classrooms become richer sites of learning and our literacies become deeper when we teach for accident wisdom. Works Cited Barth, John. The Last Voyage of Somebody the Sailor. New York: Little Brown, 1991. Boyle, Richard. The Three Princes of Serendip: Part I. June 7, 2003. http://livingheritage.org/three_princes.htm Coleridge, Samuel Taylor. The Rime of the Ancient Mariner. The Norton Anthology of English Literature. Vol. 2. rev. New York: W. W. Norton, 1968. 215-31. Royston, M. Roberts. Serendipity: Accidental Discoveries in Science. New York: John Wiley & Sons, 1989.